Low Carbon Freight Services analysis: a review study - Deris, Shahla; Zailani, Suhaiza; Habib, Md Mamun; Mansournia, Mohammad Reza (© 2017 ExcelingTech Pub, UK., 2018)
This article was published in the International Journal of Supply Chain Management [ © 2017, © ExcelingTech Pub, UK. ] The Journal's website is at: http://ojs.excelingtech.co.uk/index.php/IJSCM/article/view/1548